Influence of Emotional Intelligence in Job Performance (Revista LIDER, 2017)
The purpose of this paper is to identify the influence of emotional intelligence in organizations today, especially considering the effect different intelligences can have related to the generation of knowledge in the organization. The problem we are trying to address with this work should answer the question: Is the maximization of employment outcomes given by the influence of the different intelligences in people of the organization? The conclusion of this essay is that there is a strong relationship between emotional intelligence and job performance; in which, the more complex the job it emotional intelligence becomes more necessary, and they can’t exist independently of one another.